OC-037 Epidemiology and resistance patterns of culture-positive spontaneous bacterial peritonitis in Leeds 2006–2008. (23rd September 2015) - Jennings, J S R; Greer, D; Croxen, F; Davies, M; Sandoe, J
Abstract : Introduction: Spontaneous bacterial peritonitis (SBP) is a life threatening infection of ascitic fluid which occurs primarily in patients with pre-existing ascites in the setting of cirrhosis. Risk factors for developing SBP include: prior episode of SBP, gastrointestinal bleeding, ascitic total protein <1.0 g/dl and Child-Pugh score.1 Causative microorganisms include members of the normal microbial flora of the gastrointestinal tract including Escherichia coli (70%), Klebsiella species (10%), Proteus species (4%), Enterococcus faecalis (4%) and Pseudomonas species (2%).1 The choice of antimicrobial therapy must take into consideration the increasing frequency of hospital acquired infections, such as Clostridium difficile infection. Aim: To identify the local epidemiology and resistance patterns of culture-positive SBP. Methods: We retrospectively assessed the culture results of all ascitic fluid samples that grew a single organism in Leeds during the 3 years 2006–2008. Patients case notes were assessed to establish a diagnosis of SBP. An ascitic fluid neutrophil count ≥ 250/mm 3 in patients with liver disease was used to confirm the diagnosis of SBP.1 2 We excluded culture-negative SBP. Results: Single organism positive ascitic cultures were identifed in 42 patients with liver disease and an ascitic fluid neutrophil count ≥250/mm 3 . Mean age 52.1 years, 32/42 male. Underlying liver disease was ALD 35/42, HCV 3/42, PBC 1/42, NAFLD 1/42, Cryptogenic 1/42 and Post transplant 1/42. At the time of diagnosis of SBP the mean ascitic total white cell count 5.25, mean ascitic neutrophil count 4.08, mean serum Na+ 129.6 mmol/l and mean serum creatinine 147 mmol/l. Overall Child score A 0, B 8/42, C 34/42 and mean MELD score 24.1. The isolated organisms were Escherichia coli 15, Klebsiella spp. 7, other coliforms 10, Gram positive organisms 8 (including Enterococcus 2, Corynebacterium spp. 2). The Gram-negative isolates were resistant to a number of antibiotics: ciprofloxacin 38% (13/34), cefuroxime 29% (10/34), amoxycillin 32% (11/34) and tazocin 17% (6/34). The 30-day mortality was 50%. Conclusion: Empirical treatment regimes need to take into account local resistance patterns. Ciprofloxacin has been widely used for treatment and prophylaxis in SBP. Resistance has now become a significant problem.